2007
DOI: 10.1007/s00417-007-0586-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and visual outcome of endophthalmitis associated with intraocular foreign bodies

Abstract: Purpose To determine the risk factors and visual outcome of endophthalmitis associated with traumatic intraocular foreign body (IOFB) removal and its allied management. Methods A retrospective review was conducted of patients with penetrating eye trauma and retained IOFB with associated endophthalmitis managed at King Khaled Eye Specialist Hospital over a 22 year period (1983 to 2004). Results There were 589 eyes of 565 patients (90.3% male; 9.7% female) which sustained ocular trauma and had retained IOFB that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
70
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 21 publications
4
70
1
4
Order By: Relevance
“…8,14,15 Other authors have demonstrated that delayed IOFBs removal was also appropriate when a primary wound was repaired promptly, with broad spectrum antibiotic administration 16,17 and no increased risk of endophthalmitis. As our medical center is a tertiary referral center, the mean time of IOFBs removal in this study was 30.7 days (median 6 days), whereas the incidence of endophthalmitis was 9.1%, which is comparable to other studies; range 0-20%.…”
Section: Discussionmentioning
confidence: 99%
“…8,14,15 Other authors have demonstrated that delayed IOFBs removal was also appropriate when a primary wound was repaired promptly, with broad spectrum antibiotic administration 16,17 and no increased risk of endophthalmitis. As our medical center is a tertiary referral center, the mean time of IOFBs removal in this study was 30.7 days (median 6 days), whereas the incidence of endophthalmitis was 9.1%, which is comparable to other studies; range 0-20%.…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast to this, it has been shown that there is no significant increase in risk of endophthalmitis in IOFB cases if treated early with a combination of broad-spectrum systemic and topical antibiotics with possible primary wound repair. In multiple injury cases, surgical delay is likely.…”
Section: Discussionmentioning
confidence: 99%
“…[2,18,[20][21][22][23][24] The general consensus is that a delay in IOFB removal increases the risk for endophthalmitis. [24][25][26][27][28][29] In contrast to this view, Colyer and colleagues [30] have reported prompt wound closure and systemic antibiotics followed by delayed removal with no reported endophthalmitis. When we compared the groups that underwent IOFB removal within 48 hours (53%) and IOFB removal after 48 hours (47%) for initial incidence of endophthalmitis, there was no significant difference.…”
Section: Discussionmentioning
confidence: 99%